PENGARUH PENDAPATAN ASLI DAERAH, SILPA DAN LUAS WILAYAH TERHADAP BELANJA MODAL DENGAN PERTUMBUHAN EKONOMI SEBAGAI PEMODERASI (Studi Pada Kabupaten/Kota Provinsi Jawa Tengah Tahun 2012-2014) - Indri Nur Wakhidati, 12.05.52.0099; Hardiningsih, Pancawati (Students Journal of Accounting and Banking, 2017)
This study aims to determine the effect of PAD, SILPA and Territory Size of the Capital Expenditure to Economic Growth As moderating the Regency / City Central Java province Years 2012-2014. The population in this study is the Regency / City Central Java province as much as 35 consisting of 29 districts and 6 municipality. The sampling technique in this research is saturated samples (census) is a sampling technique when all members of the population is used as a sample. Data were analyzed using multiple linear regression analysis. The results of hypothesis testing can be concluded that the Local Revenue, Surplus Funding Budget and Economic Growth has no effect on Capital Expenditure. The area of positive effects on Capital Expenditure. Economic growth moderating influence on the Local Revenue Capital Expenditure. Economic growth does not moderate influence on the Budget Surplus Funding Capital Expenditure.Keywords: PAD, Silpa, Broad Areas, Economic Growth and Capital Expenditures